Przestrzeń literacka jako nośnik wartości w perspektywie edukacyjnej na przykładzie powieści J.R.R. Tolkiena Hobbit, czyli tam i z powrotem - Wójcicka, Edyta (Studia Edukacyjne, 2020)
The article attempts to show the role literary space can play as a carrier of values in the literary and cultural education of students. This problem will be discussed using J. R. R. Tolkien’s The Hobbit or There and Back Again fantasy novel as an example. Research on the reception of this book in Poland by contemporary teenagers and my experience with the discussed issues have motivated me to describe a few strategies for dealing with this novel in Polish language education in axiological terms.